Performance of the soybean crop produced with on-farm and chemicals bioinputs to control pests and diseases - Rotili Junior, Rodrigo; Radons, Patrique Jardel; Redin, Marciel (Revista de Ciências Agroveterinárias, 2024)
The soybean crop is one of the most representative oilseeds in the world, and its high grain yield also means that chemical products are very widely used to control pests and diseases. In this sense, alternative forms of control such as the use of beneficial microorganisms multiplied by the farmer himself are advantageous. The study aimed to evaluate the performance of the soybean crop cultivated with the use of on-farm chemical and biological products (Bioinputs) to control pests and diseases. The experiment was conducted under field conditions in a commercial crop area under natural climate conditions with three replications for each treatment, being agrochemicals and other bioinputs. The multiplication of bioinputs took place on the field property. The plant dry matter was evaluated at the phenological stage of R2, the number of pods and the number of grains per pod and grain weight, occurred at physiological maturation. The protein grain content in soybean grains were determined. Dry matter (2515 kg ha-1), grain weight (149.3g) and grain protein (43%) showed no statistical difference between managements with agrochemicals and bioinputs. The number of pods, grains per pod and grain yield (1523 versus 2380 kg ha-1) was higher in the chemical production system, which may be associated with the water deficit that occurred during the experiment, disfavoring the microorganisms of the bioinputs. Therefore, compared with crop bioinputs, chemical management presented higher soybean grain yield (36%) in a year of water deficit.